Acute toxicity and early cosmetic outcome in patients treated with multicatheter balloon brachytherapy with skin spacing ≤ 7.0 millimeters - Lee, Kiwhoon; Quillo, Amy; Dillon, Dustin; Sowards, Keith; Hatmaker, Allison; Dragun, Anthony (Journal of Contemporary Brachytherapy, 2012)
Purpose : To review institutional experience treating patients who underwent breast conserving surgery and adjuvant accelerated partial breast irradiation with multilumen balloon brachytherapy (MLB) with close skin spacing (≤ 7 mm). Material and methods : Since July 2009, 26 patients with skin spacing ≤ 7.0 mm were treated with breast-conserving therapy and adjuvant MLB brachytherapy. Patients were treated with either the Contura or MammoSite ML catheter to a total dose of 34 Gy in 10 fractions. Patients were assessed for acute toxicity at the completion of treatment and 1-month post treatment. Cosmesis and late toxicity were assessed at three-month intervals thereafter. Results : The median age of the patients was 56 years and median follow-up was 9 months. Sixteen patients had skin spacing of 5.0-7.0 mm, 10 with < 5.0 mm (median 5.8). The median percentage of the target (PTV_EVAL) receiving  95% of the prescription dose was 95.6%. The median volume of PTV_EVAL receiving  200% of the prescription dose was 6.1 cc. The maximum skin dose was 118.2% (median). The most commonly observed acute toxicity was grade 1-2 dermatitis (65.4%). The rate of post-treatment seroma and infection was 38.5% and 3.8%, respectively. Excellent/good cosmetic outcomes seen at the time of last follow-up was 92.3%. Conclusions : MLB brachytherapy is safe and feasible in patients with close skin spacing, with acute toxicity and early cosmesis similar to other published series. These devices may broaden the application of balloon brachytherapy in patients previously excluded from this treatment based on anatomy.